2008
DOI: 10.1038/ki.2008.24
|View full text |Cite
|
Sign up to set email alerts
|

Effective and safe treatment with cyclosporine in nephrotic children: A prospective, randomized multicenter trial

Abstract: We conducted a prospective, open-label multicenter trial to evaluate the efficacy and safety of treating children with frequently relapsing nephrotic syndrome with cyclosporine. Patients were randomly divided into two groups with both initially receiving cyclosporine for 6 months to maintain a whole-blood trough level between 80 and 100 ng/ml. Over the next 18 months, the dose was adjusted to maintain a slightly lower (60-80 ng/ml) trough level in Group A, while Group B received a fixed dose of 2.5 mg/kg/day. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 31 publications
4
43
0
5
Order By: Relevance
“…Numerous studies have documented the prevalence of CsAN in patients who were treated for idiopathic nephrotic syndrome. Since 1986, Ͼ200 follow-up biopsies in patients who were treated with CsA for SDNS have been reported in the literature (1,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These studies are difficult to compare because they vary in the number of biopsies, underlying renal pathology, duration of follow-up, dosages of CsA, and criteria to define CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have documented the prevalence of CsAN in patients who were treated for idiopathic nephrotic syndrome. Since 1986, Ͼ200 follow-up biopsies in patients who were treated with CsA for SDNS have been reported in the literature (1,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). These studies are difficult to compare because they vary in the number of biopsies, underlying renal pathology, duration of follow-up, dosages of CsA, and criteria to define CsAN.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of cyclosporine in children with frequently relapsing nephrotic syndrome (FRNS) and steroid-dependent nephrotic syndrome (SDNS) have been demonstrated in a number of studies, including a randomized controlled trial (1)(2)(3)(4)(5)(6)(7)(8). We previously showed that microemulsified cyclosporine administered according to our treatment protocol is safe and effective in children with FRNS (2).…”
Section: Introductionmentioning
confidence: 93%
“…Treatment with cyclosporin A (CsA) is highly effective in maintaining remission in patients with FR-SSNS allowing withdrawal of corticosteroids, but most patients relapse after withdrawal of CsA. 8 Importantly, prolonged CsA therapy is accompanied by time-and dose-dependent nephrotoxicity. 9 Mycophenolate mofetil (MMF), the prodrug of mycophenolic acid (MPA), is a non-nephrotoxic immunosuppressive drug with inhibitory effects on T and B lymphocytes, cellsurface markers, and cytokine gene expression 10 and has proven efficacy and tolerability in renal allograft recipients.…”
mentioning
confidence: 99%